The mediating effect of business ethics in the relationship between total quality management and sustainable performance: perspective from 4- and 5-stars hotels - Sin, Kit Yeng; Choon, Ling Sim; Yi, Jin Lim; Lee, Damien; Joanne Shaza, Janang (Inderscience Enterprises Ltd, 2021)
Sustainability and ethical issues in hotel industries have received great attention in recent years. This report is the outcome of a field research, which aimed to determine the relationship between TQM, business ethics and sustainable performance. The focus of this research is 4- and 5-stars hotels in Malaysia, in which 162 4- and 5-stars hotels are sampled. Quantitative approach is adopted in which structural equation modelling is employed to assess the relationship between TQM practices, business ethics and sustainable performance. The findings of this study indicate that TQM has positive impact on sustainable performance. Hence, it is concluded that the hoteliers in Malaysia are vigorously focusing on implementation of TQM practices in order to achieve sustainability. Besides, these research findings show that business ethics play as the role of mediator in the relationship of TQM and sustainable performance. The proposed framework serves as a guideline to verify the significance of TQM practices as well as business ethics in order to leverage the hotels' sustainable performance.